Transmissible Venereal Tumor Associated with Cutaneous Metastasis and Leishmaniasis in a Bitch - Diamantino, Leidiane Uchôa Soares; Oliveira, Angélica Prado de; Andrade, Kaenna dos Santos; Santos, Marcos Wilker da Conceição; Pereira, Zayan Silva; Mendonça, Filipe Lucas de Melo; Alves da Silva Vieira, Layze Cilmara (Acta Scientiae Veterinariae, 2021)
Background: The Transmissible Venereal Tumor (TVT) is a round cell neoplasia, of contagious nature, common in the canine species, which mainly affects external genitalia. Despite metastasis being uncommon, the extragenital involvement can occur via the lymphatic or hematogenous route to regional lymph nodes, skin, subcutaneous tissue, nasal and oral mucosa, as well as the central nervous system. When the location of the tumor is genital the clinical diagnosis can be conclusive, however if it presents extragenital forms, cytological or histopathological studies are necessary for the confirmation. This work describes a case of TVT with cutaneous metastasis in a female dog with leishmaniasis. Case: A 3-year old crossbred female dog was attended at the Small Animal Medical Clinic (CMPA) of the University Veterinary Hospital (HVU) of the Federal University of West Bahia (UFOB), Barra Multidisciplinary Center. This neutered bitch dewormed, never vaccinated, rescued from the streets at the age of two and a half, had a prior history of ehrlichiosis and pyometra. The owner reported apathy, anorexia, cachexia, depression and sternal decubitus of the animal, as well as episodes of vomiting and recurrent fever. During the physical examination were observed respiratory and heart rates within normality ranges, with predominance of slightly pale mucous membranes, reactive left prescapular lymph node and subcutaneous nodular mass, not adhered to the musculature, located in the medial portion of the thirteenth left rib. Were also evidenced onychogryphosis, opaque, shineless and brittle fur, with pruritic and lichenified exfoliative dermatitis in the left scapular region, ear tips and snout, presence of a discreet quantity of brownish-colored vulvar discharge with a putrid odor. In the cytological examination, was verified the presence of cells with characteristics of TVT located in the genital mucosa, developing atypical metastasis in the cutaneous tissue in the region of the thirteenth rib, and by means of the cytomorphometric analysis of the extracellular matrix of the left popliteal lymph node, confirmed positivity for leishmaniasis. The symptomatic treatment was started aiming to restore the patient for subsequent treatment of the TVT and leishmaniasis, however, due to the non-responsiveness and worsening of the clinical picture, the owner opted for the euthanasia of the animal. Discussion: It is possible to conclude that the TVT can affect extragenital locations, although it is considered to be rare. Emphasizing that the canine species is regarded as an important reservoir of Leishmania sp., with a prominent role in the maintenance and interaction between the cycle of the disease, attention is drawn in this case for the risk to One Health, as the contact of this dog with phlebotomines, may have enabled, whilst alive, the perpetuation and transmission of the disease to other susceptible animals and human beings. As they are distinct diseases, but with pronounced rates of immunosuppression, when TVT and leishmaniasis occur in association, they generate a concerning state of debility which hinders the adoption of efficient therapeutic measures for both illnesses. Cytology is a diagnostic technique, which should whenever possible be routinely associated to the clinical examination in the veterinary practice, as it is of easy performance, low cost and great value in the determination of the diagnosis of neoplasia, identification of parasites and several other affections.